INFLUENCER MARKETING AUTHENTICITY: A MULTI-METHOD STUDY ON FOLLOWER DISCERNMENT AND ITS IMPACT ON PERSUASION KNOWLEDGE - Samapto; Lukmanul Hakim; Tibrani (RADJA PUBLIKA, 2026)
This study examines the role of authenticity in influencer marketing and investigates how follower discernment shapes persuasion knowledge and consumer responses. As influencer marketing continues to expand across digital platforms, authenticity has become a critical determinant of trust, engagement, and effectiveness. Drawing on a multi-method research design that integrates surveys, experiments, and content analysis, this study explores how followers identify cues of authenticity and sponsorship in influencer content. The findings reveal that detection cues such as language, tone, and visual consistency play a key role in shaping authenticity perceptions, while individual factors such as experience and media literacy influence the ability to discern persuasive intent. The study further demonstrates that perceived authenticity and persuasion knowledge act as central mediators, determining whether consumers respond with trust or skepticism. The activation of persuasion knowledge often leads to increased critical evaluation and resistance, particularly when content is perceived as overly commercial. However, authenticity and transparent disclosure can mitigate these effects and sustain engagement. The study contributes to theory by extending the Persuasion Knowledge Model to influencer contexts and offers practical insights for designing authentic and effective influencer strategies. Future research should explore cross-platform and cultural variations in authenticity perception.